Corrosion effect of the main rebar and stirrups on the bond strength of RC beams. (August 2021) - Moodi, Yaser; Sohrabi, Mohammad Reza; Mousavi, Seyed Roohollah
Abstract: Spliced region is a place where the concrete-rebar bond plays a significant role, and reduced bond strength in this region negatively affects the structure safety and integrity due to corrosion. This research has studied the combined corrosion effects of the main reinforcements and stirrups in the spliced region on the concrete-rebar bond strength in lap-spliced beams. A total of 15 lap-spliced RC beams with different stirrup spacing in the spliced region failed under 4-point bending; tensile bar and stirrup corrosions were the variables in this study. Finally, Response Surface Methodology (RSM) was used for estimating the relative bond strength of this beams. According to the results, adding corroded stirrups in the spliced region will cause negative effects on the bond strength in beam specimens via combined tensile bar-stirrup corrosion in the spliced region. Gradients in the descending part of the curve for relative bond strength versus corrosion were calculated at −0.0154, −0.016 and −0.017 when stirrups are 1, 2 and 3, respectively. Also, beams with 25% corrosion have the largest increase in the stirrup-induced bond strength. The results show that the model presented by RSM is in good agreement with the experimental results.